The heats of precipitation of the lead halides - Vergara, Lilia (Francisco) 1933- (s.n.], 1968)
This study aims to show the trend in the heats of precipitation of the lead halides down the halide family and to present some teaching materials making use of this observed trend in the heats of reaction. This paper describes a relatively crude and simple calorimeter which students can make themselves and an experiment which makes use of chemicals available in most drugstores.